Vulnerability and Volition in the Testamentary Law of Undue Influence and Captation - Campbell, Angela (Revue générale de droit, 2021)
This article examines how contemporary analyses of vulnerability theory are reflected in legal approaches to undue influence and captation in the Canadian common law of wills and estates and in the Civil Code of Québec in the law of succession. Critical theorists point to the risks of assuming that vulnerability lies exclusively with the elderly and persons with disabilities. The equation risks oversimplifying matters, which could compromise the equality and dignity of members of these groups. There is also a risk of overlooking the harm that may be suffered by those who are victims of social or economic oppression. A more nuanced approach posits that vulnerability is a common human trait that cuts across social identities and experiences. Due to prevailing assumptions about vulnerability, this article hypothesizes that challenges to wills based on undue influence and captation will most often occur when the testator is elderly and/or has a disability at the time of execution of the will. Canadian common law and Quebec civil law jurisprudence are examined to assess this hypothesis. This analysis reveals that certain conditions do give rise to triggers heightened judicial scrutiny of wills, but that they do not in and of themselves determine legal outcomes. The case law thus suggests a moderate—but tempered—risk that courts will draw presumptions about age and capacity when assessing the presence of undue influence or captation. Perhaps more significant is the absence of challenges to wills involving young and healthy testators. Jurists might therefore wonder whether we are at risk of overlooking some cases of untoward conduct due to the conceptual associations we make between age, incapacity and vulnerability.